2005
DOI: 10.2308/jis.2005.19.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance for Ambiguity and IT Competency among Accountants

Abstract: The accounting profession must attract and retain individuals with the interest, attitudes, and competencies demanded by the marketplace. This paper examines the influence of tolerance for ambiguity, computer anxiety, and gender on interest in acquiring IT competency among 123 accounting and AIS majors. In comparison to individuals majoring in accounting, the AIS majors were more tolerant of ambiguity (p = .025) and had slightly more positive attitudes toward computers. However, neither computer anxiety (p = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…In addition, respondents moderately agreed that ICTs have lead to public accountants providing a greater level of assurance and have allowed the accounting profession to be more transparent and accountable. These findings were similar to that found by past research (Chang & Hwaug, 2003;Hunton, 2002;Jordan, 1999) and corroborated the results of Lamberton, Fedorowicz and Roohani (2005). …”
Section: Significant Differencessupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, respondents moderately agreed that ICTs have lead to public accountants providing a greater level of assurance and have allowed the accounting profession to be more transparent and accountable. These findings were similar to that found by past research (Chang & Hwaug, 2003;Hunton, 2002;Jordan, 1999) and corroborated the results of Lamberton, Fedorowicz and Roohani (2005). …”
Section: Significant Differencessupporting
confidence: 92%
“…The transition from a non ICT environment to an ICT based working environment for those practitioners whom have not been introduce to ICT at collage has not come as easy. Lamberton, Fedorowicz and Roohani (2005) found that accountants with high Tolerance for Ambiguity (TOA) tended to accept the change towards computers more readily than accountants with low TOA levels; however, the recruiting practices in the profession have favored individuals with more conservative attitude towards risk for certain accounting and auditing positions and with good reason. Hence, the profession is dominated by individuals who are resistant to change toward more ICT usage.…”
Section: The Impact Of Icts In the Accounting Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that investigated the personalities of accountants suggests that accountants are not homogeneous in terms of ambiguity tolerance (Elias, 1999;Johnson, Kaplan, & Reckers, 1998;Majid & Pragasam, 1997). Lamberton, Fedorowicz, and Roohani (2005) examined the tolerance for ambiguity to determine if there are significant differences between individuals primarily interested in acquiring traditional financial/assurance knowledge and those interested in both accounting and information technology (IT). Their research suggested that accountants with strong interests in IT are more comfortable with ill-defined, ambiguous problem-solving situations.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Computer anxiety is the extent to which apprehension or fear occurs when an individual is faced with the possibility of using an Information System (IS) (Simonson et al 1987;Stone, Arunachalam, and Chandler 1996) and is common among not only students but also experienced professionals (Lamberton, Fedorowicz, and Roohani 2005). Hackbarth et al (2003) found that system expertise was significantly related to ease of use and was mediated by playfulness and computer anxiety.…”
Section: H1mentioning
confidence: 99%